2019
DOI: 10.1002/we.2390
|View full text |Cite
|
Sign up to set email alerts
|

Mother wavelet selection in the discrete wavelet transform for condition monitoring of wind turbine drivetrain bearings

Abstract: Although the discrete wavelet transform has been used for diagnosing bearing faults for two decades, most work in this field has been done with test rig data. Since field data starts to be made more available, there is a need to shift into application studies. The choice of mother wavelet, ie, the predefined shape used to analyse the signal, has previously been investigated with simulated and test rig data without consensus of optimal choice in literature. Common between these investigations is the use of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The Daubechies family of mother wavelets has often been used in literature, with both an increase in performance when monitoring bearings and gears as well as increasing computational effort as the order increases . The Daubechies of order 30 and was chosen for this study has been shown to perform at a high level in a comparison of 130 different mother wavelets, while not requiring the increased computational effort of the higher order Daubechies which was shown not to significantly increase performance . The first implementation of the DWT consists of a three‐level breakdown on the low‐frequency components.…”
Section: Data Processing Methods and Bearing Failuresmentioning
confidence: 99%
“…The Daubechies family of mother wavelets has often been used in literature, with both an increase in performance when monitoring bearings and gears as well as increasing computational effort as the order increases . The Daubechies of order 30 and was chosen for this study has been shown to perform at a high level in a comparison of 130 different mother wavelets, while not requiring the increased computational effort of the higher order Daubechies which was shown not to significantly increase performance . The first implementation of the DWT consists of a three‐level breakdown on the low‐frequency components.…”
Section: Data Processing Methods and Bearing Failuresmentioning
confidence: 99%
“…Similarly, a signal-to-noise ratio based wavelet selection (SNRBWS) method is proposed in [11], and a sub-band energy to entropy based wavelet selection (SBETEBWS) method is proposed in [12]. Energy to entropy ratio, sample entropy, and sparsity index are also utilized as criteria in optimal mother wavelet selection [28][29][30].…”
Section: B Wavelet Selectionmentioning
confidence: 99%
“…In this context, a selection of a suitable wavelet function is essential for the proper trend detection. Furthermore, it is important to mention that the wavelet transformation allows for the CO 2 signal decomposition into individual decomposition levels, keeping certain trends and detail information, while the rest is irreversibly suppressed [50,51]. On the basis of this procedure, we can build the wavelet-based filter bank, allowing for the CO 2 signal decomposition in multiple levels.…”
Section: Wavelet Filtrationmentioning
confidence: 99%